Tillage and crop establishment effects on weeds and productivity of a rice-wheat-mungbean rotation - Mishra, J.S.; Kumar, Rakesh; Mondal, Surajit; Poonia, S.P.; Rao, K.K.; Dubey, Rachana; Raman, Rohan Kumar; Dwivedi, S.K.; Kumar, Rahul; Saurabh, Kirti; Monobrullah, Md; Kumar, Santosh; et al. (Elsevier, 2022)
Weeds are one of the key threats in sustaining the productivity of the rice-wheat cropping system in the Indo-Gangetic Plains. The development of sound integrated weed management technologies requires knowledge of mechanisms that influence weed flora composition and weed seedbank dynamics. A long-term study was initiated in 2015 at Patna, Bihar, India to evaluate the effect of seven tillage and crop establishment methods on weed density, weed seedbank composition, and crop productivity in rice-wheat-mungbean rotation. All the treatments included zero-till mungbean after wheat. Tillage and crop establishment methods had differential effects on weed and weed seedbank composition. In rice, zero-till direct-seeded rice recorded 62% lower emergence of Cyperus iria, 82–90% of Echinochloa colona, and 81–83% of total weeds compared to tilled systems, but the system of rice and wheat intensification favoured E. colona. In wheat, the system of wheat intensification favoured the Phalaris minor and Solanum nigrum. Zero-till rice and wheat reduced the seedbank of Trianthema portulacastrum by 95%, and total weed seedbank by 62% compared to the system of rice and wheat intensification. Nearly, 72% of C. iria seeds, 62% of grasses, and 64% of broad-leaved weeds were in 0–15 cm soil layer. Zero-till direct-seeded rice produced a 13% lower rice grain yield than conventional puddled transplanted rice. Compared to the system of wheat intensification, zero-till wheat under triple zero-till systems produced an 11.5% higher grain yield. Managing weed seedbank is a long-term endeavour. The present study revealed that tillage and crop establishment methods influence weed density and diversity. Under zero-till rice-wheat system, rice yield decreases marginally, but the system productivity maintains due to improvement in succeeding wheat yield. This system is also helpful in reducing the weed flora density and soil weed seedbank. Regular monitoring and management of emerging pests such as armyworm (Mythimna separata) are, however, required. The study suggests that the adoption of triple zero-tillage can be a viable option for reducing the weed density and weed seedbank concurrently increasing the system productivity of the rice-wheat-mungbean cropping system in eastern Indo-Gangetic Plains.